COVID 19 Influence on Performance of PT Pegadaian Area Palu During 2019-2021 Period - Tune, Moh Wirasto (Devotion : Journal of Research and Community Service, 2023)
The Covid-19 pandemic has had a significant impact on various sectors, including the financial and banking sectors. One of the financial institutions affected is PT Pegadaian Area Palu. This pandemic has drastically changed economic and business conditions, so it is necessary to conduct research to understand its effect on the performance of PT Pegadaian Area Palu. The purpose of this study is to analyze the effect of the COVID-19 pandemic on the performance of PT Pegadaian Area Palu during the 2019-2021 period. This research used a quantitative approach, while the data collection technique was carried out by literature study and questionnaires to employees of PT Pegadaian Palu Area. The research sample was selected using random sampling technique. The data collected will be analyzed using statistical analysis methods with the help of the SPSS program. The results showed that Covid-19 had a significant influence on the performance of PT Pegadaian Palu area 2019-2021 period. PT Pegadaian Palu Area has been able to turn challenges due to the Covid-19 pandemic into opportunities and maintain positive performance by focusing on employee health, increasing operational efficiency, and strong collaboration, the company has successfully faced the impact of the pandemic and is able to adapt well.